Effects of soil texture and nitrogen fertilisation on soil bacterial community structure and nitrogen uptake in flue-cured tobacco - Zheng, Meiying; Zhu, Pei; Zheng, Jiayu; Xue, Lin; Zhu, Qifa; Cai, Xianjie; Cheng, Sen; Zhang, Zhongfeng; Kong, Fanyu; Zhang, Jiguang (Scientific reports, 2021)
We tested the hypothesis that soil texture and nitrogen (N) fertilisation are the primary factors regulating the N cycle and soil bacterial community structure. The response of soil bacterial communities to N fertilisation in different textured soils might help in identifying the specific underlying mechanism and hence management of N fertiliser application in fields. We examined how N fertiliser accumulates in flue-cured tobacco and influences soil bacterial community structure in different textured soils. We conducted plot and micro-plot experimental measurements of N content in soil and tobacco samples using the KNO 3 15 N isotope technique. Soil bacterial community structure was determined using high-throughput sequencing of 16S rRNA. Nitrogen absorption and utilisation by tobacco plants were highest in sandy loam soils, followed by loam soil and clay loam. The ability of clay loam to supply N was weak during the plant growth period. Absence of fertilisation could reduce bacterial abundance in soils to various degrees. Bacterial diversity was higher in sandy loam soil than in loam soil and clay loam. Soil texture and N fertilisation significantly affected soil bacterial community structure and diversity. Proteobacteria , Acidobacteria , Firmicutes , Bacteroidetes , Actinobacteria , and Chloroflexi were the dominant bacterial phyla, while Bacillus , Nitrobacter , Nitrosospira , Nitrospira , and Rhizobium were the primary N transformation bacteria at the genus level in all treatments. However, relative abundances differed with N fertiliser application, which could lead to differential N availability and N use efficiency of tobacco among soil types. We conclude that both soil texture and N fertilisation influence N accumulation and distribution in flue-cured tobacco and thus regulate soil bacterial communities. N fertiliser application in sandy loam soil should be strictly controlled for its higher N use efficiency, soil bacterial abundance, and diversity.